Revision of Multiquaestia Karisch (Lepidoptera: Tortricidae: Grapholitini) - Aarvik, Leif; Karisch, Timm (Zootaxa, 2009)
Eight species of Multiquaestia Karisch are described and illustrated. Two additional species known from single females are figured but not described. A key to the known species is given.